901. HELIANTHUS SALICIFOLIUS: Compositae. (4th January 2019) - Hind, Nicholas; Smith, Alison
Summary: Helianthus salicifolius A. Dietr. (Compositae: Heliantheae: Helianthinae) is described and illustrated. Cultivation, propagation, pests and diseases and availability notes, of both the species and cultivars, are provided. The genus Helianthus, and the position of H. salicifolius is commented on, as well as its similarity to H. angustifolius . Distinguishing characters between these two species are given. Comments are provided on types and typification of some of the synonyms of H. salicifolius, as well as the complications of illustrating this species and compendia of references to these illustrations that have confused H. angustifolius . The presence of the natural hybrid, H. kellermannii, is also noted and discussed.